Consideraciones sobre la ordenación de montes en el Pirineo Occidental aragonés y su incidencia en el medio natural - De La Riva Fernández, Juan Ramón (Geographicalia, 2017)
The time elapsed from the beginning of the Ordenación de Montes (forest planning) in Spain makes necessary an analysis of its results and its impactin the natural environment. In the Jacetania area the wood planned exploitation, as well as the rest of the resources linked to the forest administration, was initiated in some of the municipes more than sixty years ago. After presentation of the main characteristics, the experience of planning in the zone is analysed from one of its most representative valleys: the Ansó valley, that nowadays crossesa critical moment in the management of these resources.
Keywords: Forest planning; environmental impact; Jacetania; forest